One-step synthesis of Ni3S2 nanorod@Ni(OH)2 nanosheet core-shell nanostructures on a three-dimensional graphene network for high-performance supercapacitors - Zhou, Weijia (2015)
A three-dimensional graphene network (3DGN) grown on nickel foam is an excellent template for the synthesis of graphene-based composite electrodes for use in supercapacitors. Ni(OH)2nanosheets coated onto single-crystal Ni3S2nanorods grown on the surface of the 3DGN (referred to as the Ni3S2@Ni(OH)2/3DGN) are synthesized using a one-step hydrothermal reaction. SEM, TEM, XRD and Raman spectroscopy are used to investigate the morphological and structural evolution of the Ni3S2@Ni(OH)2/3DGN. Detailed electrochemical characterization shows that the Ni3S2@Ni(OH)2/3DGN exhibits high specific capacitance (1277 F g−1 at 2 mV s−1 and 1037.5 F g−1 at 5.1 A g−1) and areal capacitance (4.7 F cm−2 at 2 mV s−1 and 3.85 F cm−2 at 19.1 mA cm−2) with good cycling performance (99.1% capacitance retention after 2000 cycles).